Regional Externalities in the Dynamic System of Three Regions - Jaakko Simonen (European Regional Science Association (ERSA), 2003)
This study presents theoretical models of the role of externalities across two and three dimensional regional economy. Two decades ago Krugman (1981) developed a model of uneven regional development. He showed that initial discrepancy in capital-labour ratios of the two adjacent, competing regions will cumulate over time, and will inevitably lead to the division into the capital-rich and capital-poor regions. Kubo (1995) presented an extension to Krugman's model by incorporating not only scale economies within the regions but also regional externalities across regions. His model provided an explanation for different regional development patterns: uneven, joint and the mix of these two. In this study Kubo's analysis is extended to study the dynamic properties of the development of the three regions instead of two regions. We characterise dynamics and the stability of steady states in the three-region model. In particular, we show under what conditions steady state is unique, and if there can be multiple steady states. We show that condition for even regional development in Kubo's model, i.e. regional externalities are stronger than scale economies in each regions, is necessary, but not a sufficient condition for even regional development in a case of three region. Our study sheds light on e.g. the regional development in Northern Finland. A few years ago the idea of the regional network of Northern Finland was launched. That idea was meant to spread the economic growth of the city of Oulu - technologically advanced core region - to smaller peripheral areas. Models of this study offer potentially interesting frameworks to analyse different regional development patterns. Furthermore, our model can be used to analyse, how the domination of core region affects the growth of peripheral regions and what kind of regional policy should be implemented to promote economic growth in the periphery. Keywords: Scale economies, regional externalities, regional development JEL classification: C61, R12
Keywords: 330